(untitled) (Journal of Bangladesh Academy of Sciences, 2024)
In this modern technological world, several problems arise daily, whose maximum problems have been unsolved in a classical way because of their ambiguity. To solve those problems, the applications of fuzzy mathematics are increasing rapidly, whereas traditional classical methods have failed. Here, we have modified Cramer’s rules method for solving the non-square coefficient matrix of the fully fuzzy system of linear equations (FFSLE) using triangular and trapezoidal LR fuzzy numbers. This modified method is compared with another method that can only solve the square coefficient matrix using fuzzy triangular and trapezoidal numbers. At last, we observe that our modified method is more general than others. This process is illustrated with numerical examples. J. Bangladesh Acad. Sci. 48(2); 147-160: December 2024